Monitoring, assessing and recommending the quality potable water on UIA campus - Kabbashi, Nassereldeen Ahmed; Muyibi, Suleyman Aremu; Fofana, Omar (IIUM Press, 2009)
Drinking water quality is of utmost importance both to public health and to conservation of water bodies. Maintenance of quality standards for potable water inhibits the spread of any waterborne disease and to protect receiving water quality. While achieving these water quality standards, it it necessary to consider the treatment that is required for such standards that is supplied to UIA Gombak campus by creating a database of life cycle inventory parameters. These parameters result from a life cycle assessment conducted on the system according to pre-determined boundaries. The system included the supply and distribution of potable water to UIA Gombak campus. For each parameter in the system, common treatment trains were developed using information from literature reviews prior to this study. The assessment required a comprehensive literature review of studies done prior to this one it also incorporated some of their analysis. In recent times there have been complaints from different quarter in UIA Gombak about the taste, smell, and color of the water supplied. At the end of this study the conclusion was reached that the water in UIA is safe to drink all the parameters were made how to improve the water standards.